2021
DOI: 10.1186/s13256-021-03066-z
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell squamous cell carcinoma exhibiting prominent neutrophil phagocytosis: a case report

Abstract: Background Spindle cell squamous cell carcinoma is an uncommon variant of squamous cell carcinoma; its diagnosis is sometimes challenging because it histopathologically resembles neoplastic or reactive spindle cell lesions of mesenchymal origins. Here, we report a rare case of spindle cell squamous cell carcinoma exhibiting prominent neutrophil phagocytosis. Case presentation A 69-year-old Japanese man presented with pain and a polypoid mass on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ezulia et al [3] have reported similar lesion in lower right alveolus which caused mild trismus similar to the present case. Yamazaki et al [6] presented a case report of pain and a polypoid mass on the lower left gingiva with associated trismus. Panoramic radiography showed bone resorption, exhibiting a moth-eaten appearance that involved the base of the mandible.…”
Section: Imagingmentioning
confidence: 99%
“…Ezulia et al [3] have reported similar lesion in lower right alveolus which caused mild trismus similar to the present case. Yamazaki et al [6] presented a case report of pain and a polypoid mass on the lower left gingiva with associated trismus. Panoramic radiography showed bone resorption, exhibiting a moth-eaten appearance that involved the base of the mandible.…”
Section: Imagingmentioning
confidence: 99%
“…The histological subtypes of OSCC comprise the following six distinct variants according to the WHO: Spindle cell carcinoma variant manifests as a biphasic tumor, comprising a SCC and a malignant spindle cell component with a mesenchymal appearance. This subtype is recognized for its aggressive behavior and rapid growth[ 4 ]. The Basaloid SCC variant is typified by a basaloid cell population and a diminished presence of squamous cells.…”
Section: Introductionmentioning
confidence: 99%